2008
DOI: 10.1267/ahc.07029
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Chromogenic In Situ Hybridisation with Fluorescence In Situ Hybridisation and Immunohistochemistry for the Assessment of Her-2/neu Oncogene in Archival Material of Breast Carcinoma

Abstract: The successful treatment of breast cancer is dependent upon a number of complex factors. Her-2/neu gene amplification is known to be one of the most common genetic alterations associated with breast cancer and its accurate determination has become necessary for the selection of patients for trastuzumab therapy. The aim of this study was to prove the consistency of chromogenic in situ hybridisation (CISH) technique after analyzing the overexpression of the Her-2/neu proto-oncogene in 100 invasive breast carcino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 20 publications
2
13
0
Order By: Relevance
“…Concordance between FISH and CISH was 100% for the eight cases analyzed. This high concordance was also found by several other studies [ 11 , 14 , 28 ]. One of the eight cases displayed a small frequency of cells showing chromosome 17 polysomy by FISH and showed a score 2+ by IHC.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Concordance between FISH and CISH was 100% for the eight cases analyzed. This high concordance was also found by several other studies [ 11 , 14 , 28 ]. One of the eight cases displayed a small frequency of cells showing chromosome 17 polysomy by FISH and showed a score 2+ by IHC.…”
Section: Discussionsupporting
confidence: 91%
“…Peiró et al [ 29 ] showed that all of the polyploidy tumors analyzed presented 2+ immunostaining. Although a limited number of cases were evaluated by FISH in the present study, the data are in agreement with other studies which indicate that the chromogenic ISH technique seems to be sensitive and specific for the detection of HER-2 amplification in human archival tumor samples [ 14 , 28 ].…”
Section: Discussionsupporting
confidence: 91%
“…The SISH method employs both HER-2 and chromosome 17 centromere probes hybridized on separate slides and is currently under review by the FDA. Numerous studies have confirmed a very high concordance between CISH and FISH, typically in the 97%-99% range [191][192][193][194][195][196][197][198][199][200][201][202][203]. Similar to FISH, CISH has its highest correlation with IHC 0, 1ϩ, and 3ϩ results and lowest correlation with IHC 2ϩ staining.…”
Section: Pitfalls In Ihc and Fish Test Interpretationmentioning
confidence: 98%
“…Other techniques of HER2 testing besides IHC and FISH analysis have previously been suggested, including chromogenic in situ hybridisation (CISH) [ 54 , 55 ], silver enhanced in situ hybridisation (SISH) [ 56 ], Q-RT-PCR [ 57 ] and multiplex ligation-dependent probe amplification (MLPA) [ 58 ]. Our study shows that SNP array should be included as a HER2 testing method as well.…”
Section: Discussionmentioning
confidence: 99%